Ultrasound monitoring of a deformable tongue-food gel system during uniaxial compression–an in vitro study. (June 2021) - Srivastava, Rohit; Mantelet, Mathieu; Saint-Eve, Anne; Gennisson, Jean-Luc; Restagno, Frédéric; Souchon, Isabelle; Mathieu, Vincent
Abstract: This study presents a novel ultrasound method for exploring the mechanical deformability of artificial tongue models (ATMs) topped with agar and/or gelatin food gels during uniaxial compression. The ATMs were made from polyvinyl alcohol and displayed different levels of rigidity and surface roughness. We quantified deformation of the ATM-food system as it underwent compression induced by a texture analyzer. We collected real-time measurements via an ultrasound transducer (1 MHz) placed beneath the ATM, enabling to monitor non-invasively the ultrasound time of flight (ToF) and the apparent reflection coefficient (R*) of the ATM-food interface. The results on ToF reflected the tie between the level of force and ATM deformation; they were also precise enough to identify gel fracture. R* was a crucial parameter influenced by both ATM properties (rigidity, surface roughness) and food gel properties (syneresis, ability to mold to surface asperities). Highlights: Rough and deformable artificial tongue models (ATMs) were designed. Ultrasound time of flight provided real-time analysis of ATM-food deformations. Ultrasound reflection at ATM-food interface helped to monitor surface coupling. Tongue rigidity and roughness were found to be critical in food deformation. Food properties likes softness and syneresis showed impact on food-tongue coupling.